Translocations of Chromosome End-Segments and Facultative Heterochromatin Promote Meiotic Ring Formation in Evening Primroses . Issue 3 (28th March 2014) - Golczyk, Hieronim; Massouh, Amid; Greiner, Stephan
Abstract : This work reveals the arrangement of rRNA genes, euchromatin, and heterochromatin in cycling and noncycling cells of evening primroses. The results suggest a model of chromosomal evolution, with translocations of chromosome end-segments and selection against structurally heterozygous bivalents as mechanisms that promote permanent multichromosomal rings at meiosis. Abstract: Due to reciprocal chromosomal translocations, many species of Oenothera (evening primrose) form permanent multichromosomal meiotic rings. However, regular bivalent pairing is also observed. Chiasmata are restricted to chromosomal ends, which makes homologous recombination virtually undetectable. Genetic diversity is achieved by changing linkage relations of chromosomes in rings and bivalents via hybridization and reciprocal translocations. Although the structural prerequisite for this system is enigmatic, whole-arm translocations are widely assumed to be the mechanistic driving force. We demonstrate that this prerequisite is genome compartmentation into two epigenetically defined chromatin fractions. The first one facultatively condenses in cycling cells into chromocenters negative both for histone H3 dimethylated at lysine 4 and for C-banding, and forms huge condensed middle chromosome regions on prophase chromosomes. Remarkably, it decondenses in differentiating cells. The second fraction is euchromatin confined to distal chromosome segments, positive for histone H3 lysine 4 dimethylation and for histone H3 lysine 27 trimethylation. The end-segments are deprived of canonical telomeres but capped with constitutive heterochromatin. This genomic organization promotes translocation breakpoints between the two chromatin fractions, thus facilitating exchanges of end-segments. We challenge the whole-arm translocation hypothesis by demonstrating why reciprocal translocations of chromosomal end-segments should strongly promote meiotic rings and evolution toward permanent translocation heterozygosity. Reshuffled end-segments, each possessing a major crossover hot spot, can furthermore explain meiotic compatibility between genomes with different translocation histories.